Assessment of variability and performance of new landraces of small cardamom (Elettaria cardamomum Maton) - V.V. Radhakrishnan, P.R. Akhila; K.V. Mohanan, K. Pradipkumar (Journal of Plantation Crops, 2017)
Even though fourteen improved varieties of small cardamom have been released in India so far, many of the farmers in the traditional cardamom tracts still use farmer selected landraces as planting material and hence the importance of landraces is not questionable. Four new landraces of small cardamom identified from Idukki district of Kerala State of India namely Pulari, Pappalu, Kalarikkal Bold and Arjun were evaluated along with Njallani Green Gold (popular landrace) and ICRI-2 (improved variety released by Indian Cardamom Research Institute) for growth, yield and quality characters. Eight growth characters, eight yield characters and eleven quality characters were analyzed for the purpose and all of them except two yield characters showed statistically significant variation indicating the occurrence of significant genotypic difference between these landraces. A comparative analysis of overall performance of the four landraces was also carried out and the results showed that Pappalu, Kalarikkal Bold and Pulari performed significantly superior to Njallani Green Gold and ICRI-2, the controls. Pappalu showed 132.22 per cent increase in yield over Njallani Green Gold and 158.02 per cent over ICRI-2. The cumulative performance indices of all the new landraces were worked out and the landrace Pappalu had the highest performance index of 30.06 followed by Kalarikkal Bold (27.45), Arjun (25.57) and Pulari (24.14). All the four new landraces have been found to be superior to ICRI-2 while Pappalu, Kalarikkal Bold and Pulari showed superiority over Njallani Green Gold, under preliminary evaluation.